Chronotype and Seasonality: Morningness is Associated with Lower Seasonal Mood and Behavior Changes in the Old Order Amish - Zhang, Layan (J Affect Disord, 2014)
BACKGROUND: Several studies documented that lower scores on the Morningness-Eveningness Questionnaire (MEQ) are associated with a higher global seasonality of mood (GSS). As in the Modern Man artificial lighting predominantly extends evening activity and exposure to light, and as evening bright light phase is known to delay circadian rhythms, this chronic exposure could potentially lead to both lower Morningness as well as higher GSS. The aim of the study was to investigate if the MEQ-GSS relationship holds in the Old Order Amish of Lancaster County, PA., a population that does not use network electrical light METHODS: 489 Old Order Amish adults (47.6% women), with average (SD) age of 49.7(14.2) years, completed both the Seasonal Pattern Assessment Questionnaire (SPAQ) for assessment of GSS, and MEQ. Associations between GSS scores and MEQ scores were analyzed using linear models, accounting for age, gender and relatedness by including the relationship matrix in the model as a random effect. RESULTS: GSS was inversely associated with MEQ scores (p=0.006, adjusted). LIMITATIONS: include a potential recall bias associated with self-report questionnaires and no actual light exposure measurements. CONCLUSION: We confirmed the previously reported inverse association between MEQ scores and lower seasonality of mood, for the first time in a population that does not use home network electrical lighting. This result suggests that the association is not a byproduct of exposure to network electric light, and calls for additional research to investigate mechanisms by which Morningness is negatively associated with seasonality.